PENGARUH PENGGUNAAN MEDIA PUZZLE PECAHAN PADA SISWA KELAS III SDN PUCANGSIMO I - Rusdiana, Rina; Basir, Udjang Pairin M.; Nuruddin, Muhammad (IJPSE : Indonesian Journal of Primary Science Education, 2020)
The study was backed by teachers who did not use the learning media while learning to teach and students felt difficulties in remembering and understanding fractional matter so that many students gained value under the embassy. Based on the background, the research aims to describe the influence of the use of media puzzles on student learning outcomes. This method of research is Pre-Experimental Design with One Group Of Pre-Test Post-Test which only involve one class. The purpose of this research is to learn the students ' learning outcomes before and after using the media puzzle in grade III students at SDN Pucangsimo 1. The samples in this study were grade III students numbering 49 children. This study was conducted for two meetings with a 1-week time interval. The results showed that in pretests activities (without using media) There are 30 students in the category of incomplete, there are 10 students who are in the category completed or reach the value of the KKM and there are 9 students who value above the KKM. As for the average student learning results when Pretests reaches 68 in the classical has not fulfilled the KKM, while in post-test activities There are 35 students who obtained a value above the KKM with an average of 83. The influence of learning the fractional material mathematics of grade III students at SDN Pucangsimo 1 shows that there is a significance difference of 0.00 smaller than the significance of 0.05 (0.000 < 0.05), then the hypothesis (H1) in this study was declared acceptable. This means that the variable use of media puzzles affects students ' learning outcomes before and after using the media puzzle in the learning process.